Assessment of Biosecurity Status in Commercial Chicken Farms Found in Bishoftu Town, Oromia Regional State, Ethiopia - Abdulbari Ismael; Adem Abdella; Shihun Shimelis; Asamenew Tesfaye; Yimer Muktar (Veterinary Medicine International)
A survey was undertaken from December 2017 to April 2018 to assess the biosecurity status of 44 commercial chicken farms established in Bishoftu town, Ethiopia, by interviewing farm owners using a structured questionnaire. The obtained data were summarized using frequency tables and analyzed with Pearson’s chi-square test and Fischer’s exact value using Stata 14 statistical software. From the assessed chicken farms, 31 (70.45%) were located within 0–50 m from the main road, 39 (88.64%) situated 500 m from the nearest farms, and 27 (61.36%) placed within 0–20 m from the residential areas. Forty-one (93.18%) participants disclosed that their employees did not receive training on biosecurity. From the assessed chicken farms, 30 (68.18%) had fences, 40 (90.91%) had footbaths at their gates, 31 (70.45%) prohibited visitors entrance, and 39 (88.64%) did not exchange equipment with other farms. In addition, 26 (59.09%) farms were easily accessed by wild birds, each of 42 (95.45%) farms purchased day-old chicks and feed, and 40 (90.91%) shared trucks with other farms as well. Among the assessed farms, only 2 (4.55%) had signages to restrict people’s access, 9 (20.45%) had isolation rooms for diseased chickens, 14 (31.82%) disposed of dead birds properly, and 10 (22.73%) kept various types of records. Occupation (Fischer’s exact value = 8.40; P=0.019), previous training (Fischer’s exact value = 4.40; P=0.044), source of the premises (χ2 = 5.50; P=0.019), and farm capacity (Fischer’s exact value = 13.50; P=0.002) were found statistically significantly associated with the farm biosecurity status. The farm biosecurity status was found to be good in farms that were run by civil servants, had trained employees, are owned premises, and were of large and medium scales. In conclusion, the higher poor biosecurity status on chicken farms calls for the implementation of good biosecurity practices in each farm as well as the provision of training to the farm owners and their employees.